3D TECHNOLOGIES - A MODERN APPROACH TO AUTOMATED DESIGN AND TECHNOLOGICAL ENGINEERING ENTERPRISES IN THE GRAIN STORAGE INDUSTRY - SOKOLOVSKAYA, OLENA; VALEVSKAYA, LYDMILA; SHOFUL, IGOR (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Today, enterprises of various industries, including enterprises in the grain storage industry, are faced with the need for reconstruction, modernization and expansion of production. However, the implementation of such projects is often not possible, since the exact design documentation is either completely absent or outdated and does not meet modern requirements. Moreover, today an increasing number of projects are being carried out in a three-dimensional environment and simple flat drawings are no longer a sufficient basis for design.3D design is a huge step forward in engineering and its use significantly increases the competitiveness of a design organization in the market. 3D technologies are one of the most important areas of design automation, no one has any doubts about the need to use them both at the design stage and directly during the construction of industrial facilities.Choosing the optimal simulation software is often difficult, as it is not easy to find a program that has all the necessary functionality. In the course of the research we analyzed the possibilities of several popular programs for 3D modeling and the possibility of their use in the process of designing enterprises in the field of grain storage.Thanks to the use of three-dimensional technology, the enterprise gets the opportunity to implement the project in a better quality and in a shorter time, to find errors even before the production of prototypes, and after all, correcting various shortcomings at the design stage is hundreds of times cheaper than at the production stage. Another advantage of 3D models is that they can be transferred to pre-production systems that automatically create programs. This significantly speeds up the production cycle.3D-design of the elevator becomes a necessity: this is the only way to quickly make a complete virtual model of the elevator with all the nodes, where you can see the route of the grain through the future elevator. This avoids many of the errors that occur when designing only on the basis of a linear model.
Keywords: software; design; 3D technology; 3D model; computer-aided design systems